5α‐reductase type 3 enzyme in benign and malignant prostate. Issue 3 (22nd October 2013) - Titus, Mark A.; Li, Yun; Kozyreva, Olga G.; Maher, Varun; Godoy, Alejandro; Smith, Gary J.; Mohler, James L.
Abstract BACKGROUND Currently available 5α‐reductase inhibitors are not completely effective for treatment of benign prostate enlargement, prevention of prostate cancer (CaP), or treatment of advanced castration‐recurrent (CR) CaP. We tested the hypothesis that a novel 5α‐reductase, 5α‐reductase‐3, contributes to residual androgen metabolism, especially in CR‐CaP. METHODS A new protein with potential 5α‐reducing activity was expressed in CHO‐K1 cellsandTOP10 E. coli for characterization. Protein lysates and total mRNA were isolated from preclinical and clinical tissues. Androgen metabolism was assessed using androgen precursors and thin layer chromatography or liquid chromatography tandem mass spectrometry. RESULTS The relative mRNA expression for the three 5α‐reductase enzymes in clinical samples of CR‐CaP was 5α‐reductase‐3 ≫ 5α‐reductase‐1 > 5α‐reductase‐2. Recombinant 5α‐reductase‐3 protein incubations converted testosterone, 4‐androstene‐3, 17‐dione (androstenedione) and 4‐pregnene‐3, 20‐dione (progesterone) to dihydrotestosterone, 5α‐androstan‐3, 17‐dione, and 5α‐pregnan‐3, 20‐dione, respectively. 5α‐Reduced androgen metabolites were measurable in lysates from androgen‐stimulated (AS) CWR22 and CR‐CWR22 tumors and clinical specimens of AS‐CaP and CR‐CaP pre‐incubated with dutasteride (a bi‐specific inhibitor of 5α‐reductase‐1 and 2). CONCLUSION Human prostate tissues contain a third 5α‐reductase that was inhibited poorly by dutasteride at high androgen substrate concentration in vitro, and it may promote DHT formation in vivo, through alternative androgen metabolism pathways when testosterone levels are low. Prostate 74:235–249, 2014. © 2013 Wiley Periodicals, Inc.